The official SAT study guide : for the new SAT. - College Entrance Examination Board ([S.l.] : Distributed by Holt, 2004)
Provides study tools for the SAT, including subject reviews, tips for different types of questions, and eight full-length practice tests with answer keys.
"CollegeBoard SAT.".
Rev. ed. of: 10 real SATs. c1997.
Young Adult
Keywords: SAT (Educational test) -- Study guides; SAT (Educational test) -- Study guides